Aluminum nitride sintered granules
Patent Information
- Application Number
- JP2021049076
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-23
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2041-03-23
AI Technical Summary
【0010】 本発明の特定窒化アルミニウム顆粒は、焼結顆粒の球形度は維持したまま、表面に凸部を形成した形状を成しているため、樹脂中に高充填でき、かつ粒子間の接触面積が大きい粒子であり、単独で、或いは、他の窒化アルミニウム粒子と組み合わせて構成される窒化アルミニウム粉末は、樹脂に充填して得られる樹脂組成物に高い熱伝導性を付与できる。
Smart Images

Figure 0007645676000003 
Figure 0007645676000004 
Figure 0007645676000005
Abstract
Description
[Technical field]
[0001] The present invention relates to novel sintered aluminum nitride granules, and more particularly to sintered aluminum nitride granules that are useful as a filler for heat dissipating materials to be filled into resins, greases, adhesives, paints, etc. to improve heat dissipation. [Background technology]
[0002] In recent years, the integration and density of electronic components has increased, and the performance requirements for heat dissipation materials have risen. Because aluminum nitride has excellent electrical insulation and high thermal conductivity, resin sheets, greases, adhesives, paints, etc. that contain aluminum nitride powder as a filler are expected to be heat dissipation materials with high thermal conductivity and high electrical insulation.
[0003] In order to improve the thermal conductivity of the heat dissipating material, it is important to use a filler with high thermal conductivity and to form many thermal conduction paths in the heat dissipating material. In general, the heat conduction paths are increased by highly filling the filler and increasing the frequency of contact between the filler particles. For this reason, there is a strong demand for aluminum nitride powder with excellent filling properties. As such a powder, sintered granules are known, which are formed by molding aluminum nitride powder into granules and then sintering them (see, for example, Patent Documents 1, 2, and 3). Sintered granules have high sphericity and a smooth surface, so they have excellent filling properties and can impart high thermal conductivity to the heat dissipating material. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent Publication No. 2003-267708 [Patent Document 2] Patent Publication No. 03-295863 [Patent Document 3] Patent Publication No. 11-269302 Summary of the Invention [Problem to be solved by the invention]
[0005] However, conventional sintered aluminum nitride granules are spherical. Compared to powders and other materials made up of irregularly shaped particles, while they have excellent packing properties, the contact area between particles is small, which poses an issue of low efficiency in forming heat conduction paths even when the packing rate is increased. [Means for solving the problem]
[0006] As a result of intensive research by the inventors to solve the above-mentioned problems, they discovered that by forming protrusions of a specific height made of an inorganic substance with high thermal conductivity at a specific frequency on the particle surfaces of aluminum nitride sintered granules, it is possible to increase the contact area between particles while maintaining the high packing ability that is a characteristic of sintered granules, and by filling this into a resin, it is possible to impart high thermal conductivity to the resulting heat dissipation material, which led to the proposal of the present invention.
[0007] That is, according to the present invention, the sintered aluminum nitride granules have a sphericity of 0.80 or more and a particle size in the range of 20 to 150 μm, and the protrusions are made of an inorganic material having a height of 3 to 10 μm and a theoretical thermal conductivity of 40 W / m K or more, and the protrusions are formed in a ratio of 2.0×10 -3 pieces / μm 2 There is provided sintered aluminum nitride granules (hereinafter also referred to as specific sintered aluminum nitride granules) characterized by having the above frequency on their surfaces.
[0008] The present invention also provides a filler for resins, which comprises aluminum nitride powder containing specific aluminum nitride sintered granules.
[0009] Furthermore, according to the present invention, there is also provided a resin composition which can realize extremely high thermal conductivity by filling the resin filler at a filling rate of 60 volume % or more. Effect of the Invention
[0010] The specific aluminum nitride granules of the present invention have a shape with convex portions formed on the surface while maintaining the sphericity of sintered granules, and therefore can be highly filled into resin and have a large contact area between particles. Aluminum nitride powder formed alone or in combination with other aluminum nitride particles can impart high thermal conductivity to the resin composition obtained by filling it into resin. [Brief description of the drawings]
[0011] [Figure 1] Electron microscope photograph showing the structure of the specific aluminum nitride sintered granules obtained in Example 2 [Diagram 2] Electron microscope photograph showing the particle structure of the aluminum nitride sintered granules obtained in Comparative Example 2 [Diagram 3] Schematic diagram for explaining a method for measuring the height of protrusions on a particle surface DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, an embodiment of the present invention will be described in detail.
[0013] The specific aluminum nitride sintered granules of the present invention are aluminum nitride sintered granules having a sphericity of 0.80 or more and a particle size in the range of 20 to 150 μm, made of an inorganic material with a theoretical thermal conductivity of 40 W / m K or more, and having convex portions in the range of 3 to 10 μm in height with a particle diameter of 2.0 × 10 -3 pieces / μm 2 The present invention is characterized in that the surface has a frequency of 100 or more.
[0014] In the present invention, in principle, "granules" and "particles" refer to individual particles, and "powder" refers to an aggregate of individual particles.
[0015] [Sphericity] The sphericity of the specific aluminum nitride sintered granules of the present invention is 0.80 or more, preferably 0.85 or more, and more preferably 0.90 or more. If the sphericity is less than 0.80, it becomes difficult to highly fill the resin. The sphericity is calculated by dividing the minor axis of the particle by the major axis of the particle, and the closer it is to 1, the closer it is to a sphere, and the easier it is to highly fill resin or grease.
[0016] As described later, the specific aluminum nitride sintered granules of the present invention are formed by forming convex portions on sintered granules which are mainly substantially spherical in shape, so that the resulting aluminum nitride sintered granules almost all have the above-mentioned sphericity.
[0017] [Particle size] The particle size of the specific aluminum nitride sintered granules of the present invention is in the range of 20 to 150 μm, preferably 25 to 100 μm. When the particles are filled in this range into a resin, the contact between the particles is effectively achieved by the protrusions, and the particles can be easily packed in high density by using the particles in combination with other particles.
[0018] [Convex parts on the surface] The height of the surface projections of the specific aluminum nitride sintered granules of the present invention is 3 to 10 μm, preferably 4 to 9 μm. If the height of the projections is smaller than this range, the contact area between the particles filled in the resin composition becomes small, and high thermal conductivity cannot be imparted. In addition, not only is it difficult to form projections exceeding 10 μm, but if such projections exist, there is a concern that the three-dimensional hindrance between the particles will become large and the filling property will decrease.
[0019] The method for measuring the protrusions will be described later, but depending on the polishing position in the measurement method, the height of the highest part of the protrusions may not be observed. However, if the height at the measurement position exceeds 3 μm, the height of the highest part of the protrusions (the top of the protrusions) is higher than that.
[0020] In the specific aluminum nitride sintered granules of the present invention, the number of the protrusions is 2.0×10 -3 pieces / μm 2 More than 3.0×10 -3 ~1.0×10 -2pcs, more preferably 3.5×10 -3 ~9.5×10 -3 If the number of surface projections is less than this range, the effect of increasing the contact area by the projections is insufficient, the contact area between the particles filled in the resin composition becomes small, and high thermal conductivity cannot be imparted. If the number of projections is more than this range, the specific surface area of the particles is high, and the viscosity increases during resin blending, tending to reduce the filling ability of the powder.
[0021] The substance forming the protrusions on the particle surface of the present invention is not particularly limited and may be any inorganic substance having a theoretical thermal conductivity of 40 W / m K or more, preferably 100 W / m K or more. Suitable inorganic substances include aluminum nitride, silicon nitride, silicon carbide, aluminum oxide, magnesium oxide, zinc oxide, and other substances that have high thermal conductivity and a non-flat shape that makes it easy to form protrusions. Among these, silicon nitride and aluminum nitride, which have high thermal conductivity, are particularly suitable, with aluminum nitride being particularly suitable.
[0022] The specific aluminum nitride sintered granules of the present invention are obtained as an aluminum nitride powder containing the specific aluminum nitride sintered granules by the manufacturing method described below. Most of the particles of the aluminum nitride powder, excluding a small number of small particles, specifically 90% by volume or more, particularly 95% by volume or more, are present as the specific aluminum nitride sintered granules.
[0023] The specific aluminum nitride sintered granules of the present invention can be used in the form of aluminum nitride powder obtained by production, but can also be used as an aluminum nitride powder obtained by appropriately combining and mixing aluminum nitride powders containing specific aluminum nitride sintered granules of different particle sizes, aluminum nitride powders containing aluminum nitride sintered granules of the same or different particle size and having no particle surface protrusions, aluminum nitride powders of different particle sizes and not containing aluminum nitride sintered granules, etc.
[0024] In particular, when using an aluminum nitride powder containing the aluminum nitride sintered granules of the present invention as a resin filler, it is preferable to use aluminum nitride powder having different diameters in order to increase the filling rate in the resin. As the aluminum nitride powder having different diameters, for example, aluminum nitride powder having a size of submicrons to several microns is preferably used to increase the filling rate in the resin.
[0025] In the aluminum nitride powder prepared by the above-mentioned combination, it is preferable to adjust the mixing ratio so that the proportion of the specific aluminum nitride sintered granules of the present invention is 50 volume % or more, preferably 60 volume % or more, in order to fully exhibit the functions of the specific aluminum nitride sintered granules.
[0026] [Method of manufacturing sintered aluminum nitride granules] The method for producing aluminum nitride powder containing the aluminum nitride sintered granules of the present invention is not particularly limited, but an example of a method for producing the aluminum nitride sintered granules of the present invention at a high content with good reproducibility is a method in which a mixed powder consisting of a granular compact obtained by molding aluminum nitride powder into granules of about 20 to 200 μm and an inorganic powder having an average particle size of 3 to 10 μm and a theoretical thermal conductivity of 40 W / m K or more, for forming convex portions, is degreased in an air atmosphere and then sintered in a nitrogen atmosphere.
[0027] By the above-mentioned manufacturing method, an aluminum nitride powder in which most of the particles are composed of sintered aluminum nitride granules can be obtained.
[0028] This is explained in detail below.
[0029] Aluminum nitride granular compact The aluminum nitride granular compacts that are the raw material for the aluminum nitride powder of the present invention can all be used that have an average sphericity of 0.8 or more and can be sintered to obtain a dense body by firing at 1850° C. or less. The production method is not particularly limited, but for example, the aluminum nitride powder can be produced by mixing a mixture of aluminum nitride powder, sintering aid powder, binder, dispersant and solvent to prepare a slurry, and then spray-drying the slurry.
[0030] In the above manufacturing method, the aluminum nitride powder used as the raw material is not particularly limited, but it is preferable to use one having an average primary particle size of 0.4 to 1.2 μm. If the average primary particle size is smaller than this range, the aluminum nitride powder is likely to aggregate in the slurry, causing deviations in the granular structure. If the average primary particle size is larger than this range, sintering becomes difficult, and voids remain in the granules after sintering due to insufficient sintering. If voids remain, the resin will thicken during filling, making it impossible to fill it highly.
[0031] In the above-mentioned manufacturing method, the sintering aid is not particularly limited, but it is preferable to use a rare earth metal oxide. The rare earth oxide is not particularly limited, but it is preferable to use an yttrium compound, especially yttrium oxide, from the viewpoint of thermal conductivity. In addition, the amount of the sintering aid added is preferably 2 to 6 parts by weight based on the aluminum nitride from the viewpoint of thermal conductivity and sintering promotion effect. If the amount added is less than this range, sintering does not proceed easily, and voids due to insufficient sintering remain in the granules after sintering. If the amount added is more than this range, purification of aluminum nitride does not occur easily during sintering, and the thermal conductivity of the sintered granules decreases. In addition, the sintering aid makes it easier for granules to sinter, and the amount of agglomerated powder increases.
[0032] In the above-mentioned production method, any known solvent can be used without any particular limitation. For example, acetone, ketones, alcohols such as ethanol and propanol, aromatic hydrocarbons such as benzene and toluene, and the like are preferably used.
[0033] Powder for forming convex parts The powder for forming convex portions on the surfaces of the aluminum nitride particles of the present invention is an inorganic powder having a theoretical thermal conductivity of 40 W / m K or more, preferably 100 W / m K or more, and the inorganic powders exemplified above are preferably used. Note that, depending on the substance, it may be difficult to sinter aluminum nitride with a different substance, but even in that case, the aluminum nitride granules will bond to the granule surface via the sintering aid contained in the aluminum nitride granules.
[0034] The particle diameter of the powder for forming the protrusions can be 3 to 10 μm. If the particle diameter is smaller than this range, it will be integrated with the granules during sintering, making it difficult to form protrusions of sufficient height, and if the particle diameter is larger than this range, the three-dimensional obstacles between the particles due to the protrusions will be large, and the powder packing properties will decrease. In addition, the particles constituting the powder for forming the protrusions are preferably not aggregated, and have a primary particle size of 3 to 10 μm. If the powder is aggregated, voids will remain in the protrusions after sintering, which will tend to reduce the strength of the protrusions and increase the viscosity when filled with resin.
[0035] ·Raw material mixing In the manufacturing method of the present invention, any mixing method can be used that does not destroy the shape of the aluminum nitride granules and can uniformly mix the aluminum nitride granules and the powder for forming the convex portions. The mixing device is not particularly limited, but for example, a V-shaped mixer, a W-shaped mixer, a drum-type mixer, etc. can be used.
[0036] The mixing ratio of aluminum nitride granules and powder for forming convex portions is preferably 5 to 30 parts by weight of powder for forming convex portions to 100 parts by weight of aluminum nitride granules. If the amount added is less than this range, the convex portions formed on the particle surfaces after sintering are few, the contact area between the particles filled in the resin composition is small, and high thermal conductivity cannot be imparted. If the amount added is more than this range, the convex portions formed on the particle surfaces after sintering are many, and the viscosity increases during resin blending, decreasing the filling ability of the powder.
[0037] Sintering The aluminum nitride particles of the present invention can be obtained by calcining the mixed powder in an air atmosphere to remove the binder and dispersant, and then sintering in a nitrogen atmosphere at a temperature range of 1700°C to 1850°C for 1 to 10 hours. If the calcination temperature is lower than the range, the densification of the aluminum nitride granule portion and the sintering of the powder for forming the convex portions to the granule portion tend to be insufficient. If the calcination temperature is higher than the range, not only the powder for forming the convex portions is sintered to the surface of the aluminum nitride granules, but also particles in which the aluminum nitride granules are sintered between each other tend to be generated. After the above-mentioned firing, slight fusion occurs between the aluminum nitride particles having the protrusions on the surface. If fusion occurs, the filling ability into the resin decreases, so the fusion is removed by a mild crushing treatment. The crushing method is not particularly limited, but a rotary mill, a jet mill, a vibration mill, etc. can be used. If some of the particles that formed the protrusions on the surface fall off due to the crushing treatment, they can be removed by sieving, air flow classification, etc.
[0038] [Application] Aluminum nitride powder containing the specific aluminum nitride sintered granules of the present invention can be widely used in various applications that make use of the properties of aluminum nitride, particularly as a filler for heat-dissipating materials such as heat-dissipating sheets, heat-dissipating greases, heat-dissipating adhesives, paints, and thermally conductive resins.
[0039] Examples of resins and greases that serve as the matrix of the heat dissipation material include thermosetting resins such as epoxy resins and phenolic resins, thermoplastic resins such as polyethylene, polypropylene, polyamide, polycarbonate, polyimide, and polyphenylene sulfide, rubbers such as silicone rubber, EPR, and SBR, and silicone oil.
[0040] Of these, for example, epoxy resins and silicone resins are suitable as the matrix of the heat dissipating material, and addition reaction type liquid silicone rubber is desirable for making a highly flexible heat dissipating member.
[0041] In order to improve the thermal conductivity of the heat dissipating material, it is preferable to fill the resin, rubber or oil with 60% by volume or more, preferably 70% by volume or more, and more preferably 80% by volume or more. In addition to the aluminum nitride powder containing the specific aluminum nitride sintered granules of the present invention, one or more fillers such as alumina, zinc oxide, silicon carbide, graphite, etc. may be filled in such a heat dissipating material, and the shape and particle size of the filler may be selected according to the characteristics and use of the heat dissipating material. When other fillers are blended, the ratio of the aluminum nitride sintered granules of the present invention is preferably 50% by volume or more, preferably 60% by volume or more. In addition, these fillers may be surface-treated with, for example, a silane coupling agent, phosphoric acid or phosphate. In addition, additives such as a plasticizer, a vulcanizing agent, a hardening accelerator, and a mold release agent may be further added to the heat dissipating material.
[0042] The above resin composition can be produced by mixing in a blender or mixer, and the heat dissipating material can be produced by molding the resin composition by press molding, extrusion molding, or doctor blade method, and then heat curing it. EXAMPLES
[0043] The present invention will be described in more detail below, but is not limited to these examples. Various physical properties in the examples and comparative examples were measured by the following methods.
[0044] (1) Particle size, sphericity, height and number of protrusions on the particle surface The aluminum nitride powder sample was filled into epoxy resin, the resin was poured into a mold, and cured by heat pressing to produce a sheet with a thickness of 500 μm. The sheet filled with the aluminum nitride powder was ground at 5 μm intervals, and an electron microscope photograph was taken of each ground surface.
[0045] Based on the information from the electron microscope photograph of the polished surface, the major axis (DL) and minor axis (DS) of the particle image were measured using a scale, and the ratio (DS / DL) was taken as the sphericity. The major axis value was taken as the particle size of the particle.
[0046] Based on information from the electron microscope photograph of the polished surface, the number of surface projections of the particles and their height from the surface were determined. As shown in FIG. 3, the height (h) of the projections was determined as the vertical distance from a straight line connecting the lowest points of the valleys at both ends of a projection to the apex of the projection on the contour line of the particle observed in an image of the cross section of the particle at a magnification of 5000 times. Based on information from the electron microscope photograph of the polished surface, the number of projections with a height of 3 to 10 μm was divided by the surface area of the particle to obtain the surface projection frequency (particles / μm 2 ) was calculated. The average height of the convex parts was also calculated.
[0047] (2) The proportion of specific aluminum nitride sintered particles in aluminum nitride powder Based on the measurement information of 100 random particles taken from the electron microscope photograph of the polished surface in (1) above, the volume fraction of particles having a sphericity of 0.80 or more, a particle diameter (DL) in the range of 20 to 150 μm, and a convex height in the range of 3 to 10 μm was calculated, and this was taken as the fraction (volume %) of specific aluminum nitride sintered granules.
[0048] (3) Specific surface area of aluminum nitride powder The specific surface area of the aluminum nitride powder was determined by the BET method using nitrogen adsorption with a flow type automatic surface area measuring device (Shimadzu Corporation, Flowsorb 2300 model).
[0049] (4) Average particle size of aluminum nitride powder The average particle size of aluminum nitride powder (D 50 ) was measured by dispersing the sample in sodium pyrophosphate using a homogenizer and using a laser diffraction particle size distribution analyzer (MICROTRAC MT3300 manufactured by Nikkiso Co., Ltd.).
[0050] (5) Thermal conductivity of resin molded body The sample sheet was measured by a hot disk method using a thermal property measuring device (TPS2500 manufactured by Kyoto Electronics Manufacturing Co., Ltd.).
[0051] Example 1 Aluminum nitride powder with an average particle size of 1.0 μm and yttrium oxide powder were mixed in a ratio of 100:5, and 1.0 parts by weight of hexaglycerin monooleate as a surfactant, 2.5 parts by weight of butyl methacrylate as a binder, and 100 parts by weight of toluene solvent were added and thoroughly mixed in a ball mill to obtain a slurry. The slurry thus obtained was spray-dried with a spray dryer to obtain an aluminum nitride granular compact with an average particle size of 40.5 μm.
[0052] This aluminum nitride granular compact was mixed with aluminum nitride powder (theoretical thermal conductivity 320 W / m K) having an average particle size of 4.6 μm as a powder for forming protrusions in a ratio of 100:10. The mixed powder was fired in an air atmosphere at 600°C for 5 hours to remove organic matter in the granules, and then fired in a nitrogen atmosphere at 1750°C for 5 hours. The aluminum nitride particles that had become clumpy after firing were treated in a rotary ball mill to break up the agglomerations between the particles, yielding a specific aluminum nitride powder (referred to as "specific AlN powder" in the table) having specific aluminum nitride sintered granules (referred to as "specific AlN granules" in the table) in the ratio shown in Table 1.
[0053] The specific surface area and average particle size of the specific aluminum nitride powder, and the physical properties of the specific aluminum nitride sintered granules contained in the specific aluminum nitride powder, which have a diameter close to the average particle size, such as sphericity, maximum height of surface protrusions, and frequency of surface protrusions of 3 to 10 μm, were measured and the results are shown in Table 1.
[0054] In addition, the specific aluminum nitride powder and D 50 A mixed aluminum nitride powder (ratio of specific aluminum nitride sintered granules: 76% by volume) made by mixing commercially available aluminum nitride powder with a particle size of 0.8 μm in a volume ratio of 8:2 was mixed with silicone resin (CY52-276A,B manufactured by Dow Toray Co., Ltd.) so that the filling amount was 80% by volume. The silicone resin was mixed by kneading for 15 minutes using a Labo Plastomill manufactured by Toyo Seiki Seisakusho Co., Ltd., and the resulting resin composition was filled into a mold and subjected to hot pressing at 80°C for 1 hour and 1 ton to obtain a sheet body with a thickness of 6 mm, and the thermal conductivity was measured. The results are also shown in Table 1.
[0055] Example 2 A specific aluminum nitride powder was obtained in the same manner as in Example 1, except that 101.2 μm AlN granules were used as the raw material. Figure 1 is an electron microscope photograph of the specific aluminum nitride powder obtained, and it can be seen that the particles have high sphericity and have irregularities of about 4 μm on the surface.
[0056] The specific surface area and average particle size of the obtained specific aluminum nitride powder, and for the specific aluminum nitride sintered granules contained in the above specific aluminum nitride powder, particles having a diameter close to the average particle size, the physical properties such as sphericity, maximum height of surface protrusions, and frequency of surface protrusions of 3 to 10 μm were measured and the results are shown in Table 1.
[0057] The specific aluminum nitride powder obtained in Example 1 and the specific aluminum nitride powder obtained in Example 2 are 50 A sheet was obtained in the same manner as in Example 1 using an aluminum nitride mixed powder (ratio of specific aluminum nitride sintered granules: 64 volume %) obtained by mixing a commercially available aluminum nitride powder having a particle size of 0.8 μm at a volume ratio of 1:1:1, and the thermal conductivity was measured. The results are also shown in Table 1.
[0058] Example 3 An aluminum nitride powder was obtained in the same manner as in Example 1, except that an aluminum nitride powder having an average particle diameter of 9.8 μm was used as the powder for forming the convex portions. The measurement results of the specific surface area, average particle diameter, surface convex portion height, and surface convex portion frequency of the obtained aluminum nitride powder are shown in Table 1. Furthermore, an aluminum nitride mixed powder was prepared in the same manner as in Example 1 using the obtained specific aluminum nitride powder, and a sheet body was obtained using this, and the thermal conductivity was measured. The results are also shown in Table 1.
[0059] Example 4 An aluminum nitride powder was obtained in the same manner as in Example 1, except that the mixing ratio of the aluminum nitride granules and the powder for forming the convex portions was 100:20. The measurement results of the specific surface area, average particle size, surface convex portion height, and surface convex portion frequency of the obtained aluminum nitride powder are shown in Table 1. Furthermore, the obtained specific aluminum nitride powder was prepared as an aluminum nitride mixed powder in the same manner as in Example 1, and a sheet body was obtained using this, and the thermal conductivity was measured. The results are also shown in Table 1.
[0060] Comparative Example 1 An aluminum nitride powder was obtained in the same manner as in Example 1, except that no powder for forming convex portions was added to the raw material. The results of measuring the specific surface area, average particle size, surface convex portion height, and surface convex portion frequency of the obtained aluminum nitride powder are shown in Table 1. Furthermore, using the obtained aluminum nitride powder, an aluminum nitride mixed powder was prepared in the same manner as in Example 1, and a sheet body was obtained using this, and the thermal conductivity was measured. The results are also shown in Table 2.
[0061] Comparative Example 2 Aluminum nitride powder was obtained in the same manner as in Example 2, except that no powder for forming convex portions was added to the raw materials. FIG. 2 is an electron microscope photograph of the obtained aluminum nitride powder, and it can be seen that the particles have fine irregularities of 3 μm or less on the surface. The results of measuring the specific surface area, average particle size, height of surface convex portions, and frequency of surface convex portions of the obtained aluminum nitride powder are shown in Table 2. Furthermore, the obtained aluminum nitride powder, the aluminum nitride powder obtained in Comparative Example 1, and D 50 A commercially available aluminum nitride powder having a particle size of 0.8 μm was mixed in a volume ratio of 1:1:1 to obtain an aluminum nitride mixed powder, which was used to obtain a sheet body in the same manner as in Example 1, and the thermal conductivity was measured. The results are also shown in Table 2.
[0062] Comparative Example 3 An aluminum nitride powder was obtained in the same manner as in Example 1, except that the mixing ratio of the aluminum nitride granules and the powder for forming convex portions was 100:3. The results of measuring the specific surface area, average particle size, surface convex portion height, and surface convex portion frequency of the obtained aluminum nitride powder are shown in Table 2. Furthermore, the obtained aluminum nitride powder was used to prepare an aluminum nitride mixed powder in the same manner as in Example 1, and a sheet was made using this, and the thermal conductivity was measured. The results are shown in Table 2.
[0063] [Table 1]
[0064] [Table 2] [Industrial Applicability]
[0065] The aluminum nitride powder containing the specific aluminum nitride sintered granules obtained by the present invention has a shape and particle size suitable for a filler, and therefore, when used alone or in combination with other aluminum nitride powders, it can be highly filled into a matrix such as a resin or grease, and the contact area between particles is large, so that a heat dissipation sheet, heat dissipation grease, heat dissipation adhesive, etc. with high thermal conductivity can be obtained. [Explanation of symbols]
[0066] 1 Particle outline 2. The apex of the convex part 3. Lowest point of the valley 4. Lowest point of the valley
Claims
1. Sintered aluminum nitride granules having a sphericity of 0.80 or more and a particle size in the range of 20 to 150 μm, and having a height of 3 to 10 μm and a convex portion made of an inorganic material with a theoretical thermal conductivity of 40 W / m K or more, the convex portion being 2.0×10 -3 An aluminum nitride sintered granule characterized in that it has on its surface a frequency of up to 1.0×10 −2 particles / μm 2.
2. 2. A filler for resin comprising aluminum nitride powder containing 50% by volume or more of the aluminum nitride sintered granules according to claim 1.
3. A resin composition containing the filler for resins according to claim 2 at a filling rate of 60% by volume or more.
Citation Information
Patent Citations
Production of spherical aluminum nitride powder
JP1991295863A
Filler for improving thermal conductivity of resin product and its production
JP1999269302A
Method of manufacturing aluminum nitride sintered powder
JP2003267708A
Aluminum nitride-based particle and manufacturing method therefor
JP2016037438A
Aluminum nitride granular powder
JP2019108236A